IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER DI SMP MUHAMMADIYAH 3 AMPEL KECAMATAN AMPEL KABUPATEN BOYOLALI - Ani Budi Hartanti; Ghufron Abdullah; Ngurah Ayu Nyoman Murniati (Jurnal Manajemen Pendidikan (JMP), 2020)
School is one place to shape the character of students. Character education in schools can succeed optimally if the implementation is integrated through school rules and regulations, classroom learning processes, and extracurricular activities. In addition, educators are also required to provide good behavior or character models for their students.This research aims to find out: 1) the implementation of strengthening character education in improving the religious attitudes of students in Muhammadiyah 3 Ampel Middle School Ampel District Boyolali District, 2) implementation of strengthening character education in improving student responsibility in Muhammadiyah 3 Ampel Middle School Ampel District Boyolali District , 3) barriers to implementation of strengthening character education in Muhammadiyah 3 Ampel Middle School, Ampel District, Boyolali Regency.This research uses a qualitative approach. Data collection techniques are carried out through interviews, observation and documentation studies. Procedure for data analysis with data collection, data reduction, data presentation and data verification. While the research subjects were principals, teachers, parents of students, students and alumni.The results of the research show that: 1) the implementation of strengthening character education in improving the religious attitudes of students by incorporating religious character education into the school curriculum both in school and outside the school. 2) implementation of strengthening character education in improving student responsibility by being integrated into the learning process and school programs. Integration of character education in schools is carried out with integration in self-development programs, subjects, and school culture, 3) barriers to the implementation of strengthening character education are require continuous processes and are carried out continuously. In addition, students do not have a high awareness of themselves. The conclusions of this research are: 1) strengthening character education is carried out well and continuously in an effort to improve the religious attitudes of students, 2) strengthening character education is carried out well as in an effort to improve the attitude of responsibility of students, 3) obstacles faced in implementing education reinforcement whose main character is requiring time to cultivate self-awareness. Suggestions are aimed at: 1) Teachers to motivate and assist students in strengthening character and becoming role models for students, 2) Principals are more intensive in monitoring the development of school programs related to character education. 3) students can instill more responsibility in all aspects of life.